Urban expansion impacts the surface water source of the water supply system in Belém and Ananindeua, Brazil (Research, Society and Development, 2020)
The aim of that research is to analyse the evolution of human activities close to Lake Bolonha, one of the main surface water sources for the Water Supply System in downtown Belém and Ananindeua, is investigated. Research consists of three stages. Stage 1 characterizes the environs and evaluates the importance of Lake Bolonha within the urban context. Stage 2 identifies human activities in the last ten years in the environs of the water source. Stage 3 analyzes impacts and environmental degradation risks, with special focus on vegetation around the lake. Results show that urban expansion reduced riparian vegetation and triggered sewerage flow into the lake, compromising self-cleaning capacity in the medium and long term, with an increase of pollution/contamination. The administration should develop and intensify activities to avoid irregular land occupation, establish a sewerage system and restitute the riparian vegetation lost. Lake Bolonha is highly relevant for the water supply system of approximate one million people of Belém and Ananindeua within the metropolitan region of Belém, Brazil.